The ghost crab Ocypode mortoni George, 1982 (Crustacea: Decapoda: Ocypodidae): redescription, distribution at its type locality, and the phylogeny of East Asian Ocypode species - Wong, Kingsley J. H.; Shih, Hsi-Te; Chan, Benny K. K. (Zootaxa, 2012)
The ghost crab Ocypode mortoni George, 1982 was first described from the sandy shores of Sai Wan, Hong Kong, andalthough also identified from South China and Japan, has not been subsequently recorded in Hong Kong. The taxonomicstatus of O. mortoni is not clear as its original morphological description was not detailed, and there remains no informa-tion on its vertical and horizontal ecological distribution in Hong Kong. In the present study, O. mortoni was found to belocally rare in Hong Kong, only present at three of seven surveyed sites. It was always sympatric with the common O.ceratophthalmus (Pallas, 1772) at the same tidal level, and there appeared to be no clear habitat/niche distinction. Relativeabundance of O. mortoni vs. O. ceratophthalmus was at most 31%: 69% based on quantitative transect survey data fromSai Wan. Molecular phylogenetic analyses on 24 haplotypes (from 28 individuals) of 636-basepair (bp) mitochondrial cy-tochrome oxidase I (COI) gene of Ocypode spp. in East Asia show O. mortoni is a valid species most closely related to O.stimpsoni Ortmann, 1897, with an average difference of 37.64 bp, and nucleotide divergence of 6.25%. The two species are very similar morphologically, but adults of O. mortoni develop ocular stylets.